Elimination of iron deficiency anemia and soil transmitted helminth infection: evidence from a fifty-four month iron-folic acid and de-worming program. - Gerard J Casey; Antonio Montresor; Luca T Cavalli-Sforza; Hoang Thu; Luong B Phu; Ta T Tinh; Nong T Tien; Tran Q Phuc; Beverley-Ann Biggs (Public Library of Science (PLoS), 2013)
BACKGROUND: Intermittent iron-folic acid supplementation and regular de-worming are effective initiatives to reduce anemia, iron deficiency, iron deficiency anemia, and soil transmitted helminth infections in women of reproductive age. However, few studies have assessed the long-term effectiveness of population-based interventions delivered in resource-constrained settings. METHODOLOGY/PRINCIPAL FINDINGS: The objectives were to evaluate the impact of weekly iron-folic acid supplementation and de-worming on mean hemoglobin and the prevalence of anaemia, iron deficiency, and soil transmitted helminth infection in a rural population of women in northern Vietnam and to identify predictive factors for hematological outcomes. A prospective cohort design was used to evaluate a population-based supplementation and deworming program over 54 months. The 389 participants were enrolled just prior to commencement of the intervention. After 54 months 76% (95% CI [68%, 84%]) were taking the iron-folic acid supplement and 95% (95% CI [93%, 98%]) had taken the most recently distributed deworming treatment. Mean hemoglobin rose from 122 g/L (95% CI [120, 124]) to 131 g/L (95% CI [128, 134]) and anemia prevalence fell from 38% (95% CI [31%, 45%]) to 18% (95% CI [12%, 23%]); however, results differed significantly between ethnic groups. Iron deficiency fell from 23% (95% CI [17%, 29%]) to 8% (95% CI [4%, 12%]), while the prevalence of iron deficiency anemia was reduced to 4% (95% CI [1%, 7%]). The prevalence of hookworm infection was reduced from 76% (95% CI [68%, 83%]) to 11% (95% CI [5%, 18%]). The level of moderate or heavy infestation of any soil-transmitted helminth was reduced to less than 1%. CONCLUSIONS/SIGNIFICANCE: Population-based interventions can efficiently and effectively reduce anemia and practically eliminate iron deficiency anemia and moderate to heavy soil transmitted helminth infections, maintaining them below the level of public health concern.